Cholesterol Lowering Effects of Tempe Dietary Fiber On Rats - Kiswanto, Yulius (Universitas Widya Mataram, 2025)
Tempe is a popular fermented soy product with a variety of health benefits. It’s high in protein, prebiotics and a wide array of vitamin, minerals and fiber. One of the macro componen that is dietary fiber could have beneficial effects in lowering cholesterol levels. The main goal of this experiment treated determine the tempe diet on the level of total cholesterol in rats. In this experiment 30 male Sprague Dawley rats split into 6 groups . First group treated by standard diet, second group by tempe diet and the third group by concentrate of soy fiber for four weeks. This experiment conducted using Completely Randomized Design ( CRD ) The result showed tempe diet decrease total cholesterol from 106,4 mg/dl (diet standard ) to 92,5 mg/dl (diet tempe 40%) . Tempe diet also decrease LDL cholesterol from 38,7 mg/dl (diet standard) to 19,4 mg/dl (diet tempe 40%). HDL increase from 67,7 mg/dl ( diet standard ) to 74 mg/dl (diet tempe 40%).